Operational Risk Control Strategies in Fuel Distribution Using Hirarc And FTA - Ibnu Burliyan; Melia Eka Lestani; Agus Purnomo (Eduvest - Journal of Universal Studies, 2025)
Safety in fuel oil (BBM) distribution is a top priority given the high risks that can occur, such as fires, spills, and accidents due to mechanical failures. This study analyses the factors that cause operational incidents at PT ABC, specifically truck operational accidents in fuel distribution, by applying the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) and Fault Tree Analysis (FTA) methods. Data collection was conducted through field studies and interviews with stakeholders, including drivers, mechanics, and logistics management. The results showed that the main causes of incidents included suboptimal vehicle maintenance, inappropriate tyre pressure, driver fatigue, and brake system failure. Risk analysis showed that tyre bursts had the highest risk level with a score of 10 on the risk matrix. The implementation of risk control measures, such as daily inspections (P2H), the use of tyre pressure gauges, and safety training for drivers, contributed significantly to lowering the number of operational incidents and improving on-time delivery. The implementation of stricter safety procedures resulted in improved operational efficiency at PT ABC, with a decrease in the number of incidents and the achievement of 100% on-time delivery by the final quarter of 2024. In conclusion, adherence to standard operating procedures (SOPs), regular vehicle maintenance, and increased driver safety awareness are key factors in creating a safer and more sustainable fuel distribution system